The fever code - Dashner, James 1972- (New York Delacorte Press, 2016)
"Before the trials, WICKED found Thomas, the perfect boy, to help them build the Maze and find the cure for the Flare, a disease that plagues the world. But the truth of what is really going on is a secret and Thomas must uncover it before time runs out"--
1
Keywords: JUVENILE FICTION / Action & Adventure / General; Science fiction; Survival -- Fiction